A critical discourse analysis of Trump's election campaign speeches. Issue 4 (April 2022) - Kadim, Enas Naji
Abstract: This article presents a study in critical discourse analysis of Trump's election campaign speeches. Trump's speeches against immigrants have raised controversy in the world in general and in the United States in particular. Such speeches against immigrants might motivate Native Americans to enter a racial conflict with Muslims and other non-native Americans. The study adopts Van Dijk's (1991, 1995; 2006) discourse strategies. Therefore, this study aims to show how Trump ideologically invested these discursive strategies in the positive discourse of US (Trump, the majority of American people) and the negative discourse of THEM (Obama, Obama administration, Clinton, immigrants, especially Muslims). Based on data analysis, the study found out that Trump ideologically invested the (12) discourse strategies in almost all of the selected speeches for political interests. The study is hoped to encourage politicians to stop using language that is full of racism and sectarianism, because such language has negative results on innocent civilians. Abstract : Discourse; Discrimination; Ideology; Power.